FREKUENSI ALAMI RANGKA BATANG SEMI-KAKU DENGAN EFEK GAYA AKSIAL - Ruly Irawan (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2016)
This article presents the natural frequency analysis of beam framework and axial force effect. The analysis considers the modification of mass matrix, rigidity, and geometric matrix of semi-rigid beam framework.Â  The rigidity matrix, mass, and semi-rigid geometric connecting rod were derived from polynomial Hermite modification. This paper shows an example of natural frequency of beam framework with axial force effect or not. The results of analysis were used to show the efficiency of the calculation of beam frame work model with semi-rigid connection, which results in a more realistic solution than rigid connection model. This paper also shows that the change of axial force can result in the change of natural frequency of beam framework. Besides, this method can be used to examine any building because it can calculate the effect of structural rigidity